THE EFFECT OF USING TWO METHODS OF EMBEDDING AND LEARNING THROUGH PRACTICE IN TEACHING THE SKILLS OF HANDLING AND DRIBBLING IN HANDBALL - Prof. Nassr Khalid Abdulrazzaq (Proximus Journal Publishing, 2024)
In the field of physical education, the basic goal associated with sports is to acquire and improve the basic skills in sports games. This requires the use of appropriate means, methods and techniques, as well as proper understanding of the characteristics, interests and needs of learners in order to achieve the best results. Handball is one of the sports - a practical example - that the researchers used as an example to show what the teaching method is through practice. The skills were divided into exercises (15) studied, and each skill ranged from simple to difficult. After collecting the results, the researchers conducted a statistical analysis and found that the inclusion method can achieve better results. Physical education courses must include the inclusion method recommended by the researchers in order to achieve positive results in the development of some basic handball skills. Exercises (15) were assigned to each skill, and the exercises were different for both skills; the difficulty level of these exercises ranged from simple to difficult. After collecting the results, they were statistically analyzed, and based on the analysis, the researchers clearly found that the inclusion method can achieve better results. The researchers also drew the attention of the heads of physical training to the fact that the application of this method in handball courses will definitely help to achieve positive results in the development of some basic skills in handball
Keywords: embedment method; learning through practice method; handball